Inside Back Cover: Carbon–Halogen Bond Activation by Selenium‐Based Chalcogen Bonding (Angew. Chem. Int. Ed. 39/2017). Issue 39 (26th July 2017) - Wonner, Patrick; Vogel, Lukas; Düser, Maximilian; Gomes, Luís; Kniep, Florian; Mallick, Bert; Werz, Daniel B.; Huber, Stefan M.
Abstract : Selenium compounds may form noncovalent interactions, so‐called chalcogen bonds, with Lewis bases under certain conditions. In their Communication onpage 12009 ff., S. M. Huber and co‐workers show that such chalcogen bond donors activate a benchmark reaction. Control experiments with non‐selenated reference compounds confirmed the crucial role of the selenium substituent. The corresponding brominated halogen bond donor was somewhat less active.